▼Targinact – opioid pain relief without constipation?. Issue 12 (1st December 2010) - Unknown
Abstract : ▼Targinact (Napp Pharmaceuticals Ltd) is a modified-release combination product containing the strong opioid oxycodone plus the opioid antagonist naloxone. It is licensed for "severe pain, which can be adequately managed only with opioid analgesics".1 The summary of product characteristics (SPC) states that "naloxone is added to counteract opioid-induced constipation by blocking the action of oxycodone at opioid receptors locally in the gut". Advertising for the product claims "better pain relief", "superior GI [gastrointestinal] tolerability" and "improved quality of life" "compared to previous treatment in a clinical practice study (n=7836)". Here we consider whether Targinact offers advantages over using strong opioids plus laxatives where required.